Forest Insects and Climate Change - Pureswaran, Deepa S.; Roques, Alain; Battisti, Andrea (Current forestry reports, 2018)
Purpose of Review Climate change affects populations of forest insect pests in a number of ways. We reviewed the most recent literature (2013–2017) on this subject including previous reviews on the topic. We provide a comprehensive discussion of the subject, with special attention to insect range expansion, insect abundance, impacts on forest ecosystems, and effects on forest insect communities. We considered forest insects according to their major guilds and biomes. Recent Findings Effects of climate change on forest insects are demonstrated for a number of species and guilds, although generalizations of results available so far are difficult because of species-specific responses to climate change. In addition, disentangling direct and indirect effects of climate change is complex due to the large number of variables affected. Modeling based on climate projections is useful when combined with mechanistic explanations. Summary Expansion of either the true range or the outbreak range is observed in several model species/groups of major insect guilds in boreal and temperate biomes. Mechanistic explanations are provided for a few species and are mainly based on increase in winter temperatures. In relation to insect abundance, climate change can either promote outbreaks or disrupt trophic interactions and decrease the severity of outbreaks. There is good evidence that some recent outbreaks of bark beetles and defoliating insects are influenced by climate change and are having a large impact on ecosystems as well as on communities of forest insects.